Enhancing Descriptive Writing through Outing Class: An Experimental Study - Puspitasari, Ema; Anwar, Mustofa; Sulisworo, Dwi; Hadijah, Hadijah (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
The main objective of this research is to investigate the influence of using outing class on the students’ descriptive writing ability in the eighth grade of junior high school. The population of this study consists of eighth-grade students, and the sample for this research comprises 46 students. Based on pre-survey data, the problem found can be concluded that students experience difficulties in descriptive writing because they lack ideas. Through Outing Class, students can find ideas for descriptive writing. Because with Outing Class, students gain more meaningful information and learning experiences. In this case, the author attempts to investigate whether there is an influence of using Outing Class on students’ descriptive writing skills. The author conducted a True Experimental Design by applying pre-test and post-test as instruments. In accordance with this research method, the data were analyzed using a t-test, which allows for determining the difference between the experimental group, namely the class that used the Venn diagram, and the control group that did not use the Outing Class. The research data shows that tobserves = 3.590 and this falls into the high influence category. Furthermore, tobserves is compared with ttable at a significance level of 5% = 2.010 and 1% = 2.682, the data indicates that tobservesis greater than ttable, which can be interpreted that Hi is accepted. In conclusion, the Outing Class strategy positively influences students’ descriptive writing skills. This approach provides meaningful and contextual learning experiences that promote student engagement, creativity, and improved written communication.